Tsirwah pesantren digital apps: as a da'wah platform in efforts to digitalize pesantren values - Fauziyah, Ni'matul; Adhilah, Fizna; Endiana, Yeni (UIN Salatiga, 2024)
This study aims to describe the values of pesantren in the contemporary era through the Tsirwah Pesantren Digital Application, using descriptive qualitative methods. Data was collected through a Google Form questionnaire distributed to the community and application users and observing the application in terms of presentation features, content, and user assessment. The results show that this application offers online mondok features, digital libraries, articles, and dhikr and worship features. The advantages of this application are that users can learn Islam with a clear scientific sanad in a flexible and interactive way without coming to the boarding school, but there are disadvantages such as features that are not yet optimal, yellow books that are not fully updated, and many paid features. The digitalization of pesantren values in the application includes digital yellow books, online studies, and recitation classes. The implications of the research show that the features in this application have been adapted to pesantren in the real world and are very helpful for users who want to learn without coming directly to the pesantren, with a positive response from the community who feel the benefits.